Analysis of goal scoring in Copa America 2021 - Ahmad, M. F.; Hussain, R. N. J. R.; Chik, W. F. W.; Halim, M. H. A. (Journal of Physical Education and Sport, 2022)
The most popular and influential sport across the world is called soccer. The Copa America is among the most broadly watched tournaments worldwide. In soccer, scoring a goal has become one of the most thrilling moments to observe, because it can determine the winning team. This study aims to investigate and compare the goal scoring trend (period: first half vs. second half, and area: inside vs. outside the penalty box) during the Copa America 2021 tournament. Additionally, we examined the goal scoring pattern in 28 matches (n=28), with a total of 65 goals scored (an average of 2.32 goals per match), utilizing hand notational analysis. According to the descriptive statistics, 44.6% (29 goals) were scored during the first half, while 55.4% (36 goals) were scored during the second. Additionally, 87.7% (57 goals) were scored inside the box, and only 12.3% (8 goals) were scored outside the area. As a result, there was no significant difference in the frequency of goals scored between the first and second half of the game. However, there was a significant difference in the frequency of goals scored between being inside and outside the penalty box, as scoring from inside the box was significantly higher. Future coaches should explore designing training programs that emphasize goal-scoring ability, not only for attackers, but also for midfielders and defenders. It is suggested that future research compares how goals were scored and determines their association with the playing pattern.